Ultrasound-Guided Popliteal Block Through a Common Paraneural Sheath Versus Conventional Injection: A Prospective, Randomized, Double-blind Study. Issue 3 (1st May 2013) - Perlas, Anahi; Wong, Patrick; Abdallah, Faraj; Hazrati, Lili-Naz; Tse, Cyrus; Chan, Vincent
Abstract : Background and Objectives: The macroscopic anatomy of a common paraneural sheath that surrounds the sciatic nerve in the popliteal fossa has been studied recently in a human cadaveric study. It has been suggested that an injection through this sheath could be an ideal location for local anesthetic administration for popliteal block. The aim of the present study was to evaluate the hypothesis that popliteal sciatic nerve blockade through a common paraneural sheath results in shorter onset time when compared with conventional postbifurcation injection external to the paraneural tissue. To illustrate the microscopic anatomy of the paraneural tissues, we performed histological examinations of a human leg specimen. Methods: Following institutional review board approval and written informed consent, 89 patients undergoing an ultrasound-guided popliteal block for foot or ankle surgery were included in the study. They were prospectively randomized to receive a single injection of local anesthetic at the site of bifurcation through a common paraneural sheath (group 1) or 2 separate circumferential injections of the tibial and common peroneal nerves distally to sciatic nerve bifurcation (group 2). Results: Patients in group 1 had a 30% shorter onset time of both sensory and motor block. This was associated with a more extensive proximal and distal longitudinal spread of local anesthetic in this group. Nerve diameter and cross-sectional area remained unchanged in both groups after injection, which is consistent with extraneural injection. A greater proportion of patients in group 1 required a single needle pass for block performance. Discussion: An ultrasound-guided popliteal sciatic nerve block through a common paraneural sheath at the site of sciatic nerve bifurcation is a simple, safe, and highly effective block technique. It results in consistently short onset time, while respecting the integrity of the epineurium and intraneural structures.